(untitled) (Research, Society and Development, 2025)
Sickle cell anemia is a hereditary disease characterized by the presence of hemoglobin S, which leads to sickling of erythrocytes, reduced oxygen transport, and increased clinical complications. In addition to pathophysiological aspects, socioeconomic and nutritional factors directly influence the disease’s progression, treatment adherence, and the quality of life of affected individuals. The objective of this study is to analyze the various pathophysiological, clinical, social, and therapeutic aspects related to sickle cell anemia, highlighting its repercussions on patients’ quality of life and family dynamics, as well as the importance of continuous and multidisciplinary follow-up. This study conducted an integrative literature review, searching the Google Scholar, BVS, and LILACS databases using descriptors related to sickle cell anemia and socioeconomic factors. After analyzing 68 articles, only 5 met the inclusion criteria. The results show that social vulnerability, low income, limited access to health services, and insufficient multidisciplinary support contribute to the worsening of the clinical picture. It was also observed that both malnutrition and overweight impair the overall condition of patients, reinforcing the need for nutritional monitoring. Emotional aspects, such as anxiety and depression, appear as important aggravating factors. In pregnant women, the disease is associated with higher morbidity and mortality. It is concluded that the management of sickle cell anemia should integrate social, nutritional, and healthcare interventions, with public policies that reduce inequalities and promote continuous and humanized care.